Introduction of representatives of supfamily Maloideae C. Web. (Rosaceae Juss.) in Botanical Garden of Dniepropetrovsky National University - А. М. Кабар; В. Ф. Опанасенко; Л. Л. Русецька; Д. Д. Тищенко; Є. П. Шоферістов (Plant Varieties Studying and Protection)
The present state of genofond of the collection that includes 78 taxa supfamily Maloideae C. Web. (Rosaceae Juss.) in DNU Botanical Garden.